Adaptation of rhizobacterial and endophytic communities in Citrus Grandis Exocarpium to long-term organic and chemical fertilization - Zhou, Deyang; Yang, Kaiqing; Zhang, Yinhui; Liu, Cancan; He, Ye; Tan, Jialin; Ruan, Zhepu; Qiu, Rongliang (Frontiers in Microbiology, 2024)
Introduction Organic fertilizers (OF) are crucial for enhancing soil quality and fostering plant growth, offering a more eco-friendly and enduring solution compared to chemical fertilizers (CF). However, few studies have systematically analyzed the effects of OF/CF on root microbiome of medicinal plants, especially in combination with active ingredients. Methods In this study, we investigated the composition and function of bacteria and fungi in the rhizosphere or within the root of traditional Chinese medicinal plants, Citri Grandis Exocarpium (Huajuhong), which were treated with OF or CF over 1, 3, and 5 years (starting from 2018). Additionally, we conducted metabolome analysis to evaluate the effects of different fertilizers on the medicinal properties of Huajuhong. Results The results indicated that extended fertilization could enhance the microbial population and function in plant roots. Notably, OF demonstrated a stronger influence on bacteria, whereas CF enhanced the cohesion of fungal networks and the number of fungal functional enzymes, and even potentially reduced the proliferation of harmful rhizosphere pathogens. By adopting distancebased redundancy analysis, we identified the key physicochemical characteristics that significantly influence the distribution of endophytes, particularly in the case of OF. In contrast, CF was found to exert a more pronounced impact on the composition of the rhizosphere microbiome. Although the application of OF resulted in a broader spectrum of compounds in Huajuhong peel, CF proved to be more efficacious in elevating the concentrations of flavonoids and polysaccharides in the fruit. Discussion Consequently, the effects of long-term application of OF or CF on medicinal plants is different in many ways. This research provides a guide for OF/CF selection from the perspective of soil microecology and aids us to critically assess and understand the effects of both fertilizers on the soil environment, and promotes sustainable development of organic agriculture.